The Effect of Leadership and Internal Control on the Financial Performance of the Regional Financial and Asset Management Agency of the Arfak Mountains Regency - Kasmawati Kasmawati; Theodorus Lamaurin Herin; Budiman Budiman (STIE Amkop Makassar, 2024)
This study investigates the effect of leadership and internal control on the financial performance of the Regional Financial and Asset Management Agency (BPKAD) in Arfak Mountains Regency. Effective financial performance is crucial for ensuring the efficient and transparent management of regional finances and assets. Leadership, as a determinant of strategic decision-making and organizational direction, and internal control, as a mechanism for mitigating financial risks and ensuring accountability, play pivotal roles in achieving this objective. The research employs a quantitative approach. It uses a structured questionnaire distributed to 50 respondents selected through purposive sampling, comprising key personnel of BPKAD. Data analysis uses multiple linear regression to evaluate the individual and collective impacts of leadership and internal control on financial performance. The findings indicate that both leadership and internal control significantly and positively influence financial performance, individually and collectively. Leadership emerges as the dominant factor, highlighting the importance of visionary and influential leaders in driving financial efficiency and compliance. Internal control, encompassing financial monitoring, risk management, and procedural adherence, also demonstrates a substantial effect, emphasizing its role in ensuring financial accountability and minimizing errors or misuse of resources. This study underscores the importance of strengthening leadership capacity and enhancing internal control mechanisms to improve financial performance. The results provide actionable insights for policymakers and regional governments to optimize financial management practices and ensure transparency, accountability, and efficiency in public finance administration.